Induction of hepatocellular carcinoma by in vivo gene targeting - Wang, Pei-Rong (National Academy of Sciences, 2012)
The distinct phenotypic and prognostic subclasses of human hepatocellular carcinoma (HCC) are difficult to reproduce in animal experiments. Here we have used in vivo gene targeting to insert an enhancer-promoter element at an imprinted chromosome 12 locus in mice, thereby converting ∼1 in 20,000 normal hepatocytes into a focus of HCC with a single genetic modification. A 300-kb chromosomal domain containing multiple mRNAs, snoRNAs, and microRNAs was activated surrounding the integration site. An identical domain was activated at the syntenic locus in a specific molecular subclass of spontaneous human HCCs with a similar histological phenotype, which was associated with partial loss of DNA methylation. These findings demonstrate the accuracy of in vivo gene targeting in modeling human cancer and suggest future applications in studying various tumors in diverse animal species. In addition, similar insertion events produced by randomly integrating vectors could be a concern for liver-directed human gene therapy.